From deep blue to green emitting and ultralong fluorescent copper(i) halide complexes containing dimethylthiophene diphosphine and PPh3 ligands. Issue 30 (10th July 2019) - Wei, Qiong; Zhang, Rui; Liu, Li; Zhong, Xin-Xin; Wang, Lei; Li, Guang-Hua; Li, Fa-Bao; Alamry, Khalid A.; Zhao, Yi
Abstract : Emission color can be largely tuned from deep blue to green, by changing the solid state from crystal to film. Abstract : Highly emissive copper(i ) halide complexes having thermally activated delayed fluorescence (TADF) have been paid much attention. Here, a series of four-coordinate mononuclear copper(i ) halide complexes containing both bi- and mono-phosphine ligands, [CuX(dpmt)(PPh3 )] (dpmt = 3, 4-bis(diphenylphosphino)-2, 5-dimethylthiophene, X = I (1 ), Br (2 ) and Cl (3 )), were synthesized, and their molecular structures and photophysical properties were investigated. These complexes exhibit intense deep blue emission in crystal state at room temperature and have peak wavelengths at 447–460 nm with microsecond lifetimes ( τ = 114–752 μs). Emission color can be largely tuned from deep blue to green, from crystal to film state at 293 K. The emission of the complexes1–3 mainly originates from intraligand and LLCT transitions. Solution-processed, nondoped and doped devices of complex3 exhibit yellowish green emission with CIE( x, y ) of (0.3557, 0.5031). The nondoped device gives a maximum external quantum efficiency (EQE) of 2.47% and a maximum luminance of 316 cd m −2 .